From ethical leadership to green voice: A pathway to organizational sustainability - Shanping Hu; Wafa Ghardallou; Rebecca Kechen Dong; Rita Yi Man Li; Shakira Nazeer (Acta Psychologica)
In the realm of organizational life, exchanging different resources is crucial for the success and survival of both the employer and the employee. Green voice behavior (GVB), leader-member exchanges (LMX), and perceived green organizational support (PGOS) form a part of those exchanges, i.e., munificent and constrained conditions of these resources have implications for the organizational stakeholders. To better understand those implications, we have utilized the resource theory of social exchange while delineating the relationship dynamics between environmentally specific ethical leadership (ESEL) and GVB. By examining the moderating roles of leader-member exchange (LMX) and perceived green organizational support (PGOS), we address significant gaps in understanding the mechanisms that enhance ESEL impact on GVB in organizations. A time-lagged survey of 304 middle management employees from Karachi's petroleum sector was analyzed using SPSS and AMOS. Results indicate that when leader-employee and organization-employee-based resources, i.e., LMX and PGOS were readily available in plentiful condition, employees were also generous in offering their possessed resource, i.e., green voice in response to ESEL. Whereas a resource constrained condition from leaders and organization as a whole was unable to keep employees munificent in speaking up green ideas, hence the prediction of 3-way interaction effects has been validated in the context of petroleum industry in Pakistan. The study shows a three-way interaction effect where leader-member exchange compensates for limited organizational resources.